Hepatocyte-derived liver progenitor-like cells attenuate liver cirrhosis via induction of apoptosis in hepatic stellate cells - Xu Zhou; Wen-Ming Liu; Han-Yong Sun; Yuan Peng; Ren-Jie Huang; Cai-Yang Chen; Hong-Dan Zhang; Shen-Ao Zhou; Hong-Ping Wu; Dan Tang; Wei-Jian Huang; Han Wu; et al. (Hepatology Communications, 2025)
Background:. Cell therapy demonstrates promising potential as a substitute therapeutic approach for liver cirrhosis. We have developed a strategy to effectively expand murine and human hepatocyte-derived liver progenitor-like cells (HepLPCs) in vitro. The primary objective of the present study was to apply HepLPCs to the treatment of liver cirrhosis and to elucidate the underlying mechanisms responsible for their therapeutic efficacy. Methods:. The effects of allogeneic or xenogeneic HepLPC transplantation were investigated in rat model of liver cirrhosis. Liver tissues were collected and subjected to immunostaining to assess changes in histology. In vitro experiments used HSCs to explore the antifibrotic properties of HepLPC-secretomes and their underlying molecular mechanisms. Additionally, proteomic analysis was conducted to characterize the protein composition of HepLPC-secretomes. Results:. Transplantation of HepLPCs resulted in decreased active fibrogenesis and net fibrosis in cirrhosis models. Apoptosis of HSCs was observed in vivo after HepLPC treatment. HepLPC-secretomes exhibited potent inhibition of TGF-β1-induced HSC activation and promoted apoptosis through signal transducer and activator of transcription (STAT)1-mediated pathways in vitro. Furthermore, synergistic effects between amphiregulin and FGF19 within HepLPC-secretomes were identified, contributing to HSC apoptosis and exerting antifibrotic effects via activation of the janus kinase-STAT1 pathway. Conclusions:. HepLPCs have the potential to ameliorate liver cirrhosis by inducing STAT1-dependent apoptosis in HSCs. Amphiregulin and FGF19 are key factors responsible for STAT1 activation, representing promising novel therapeutic targets for the treatment of liver cirrhosis.